Trained immunity: novel perspectives in diabetes and associated complications - Liu, Yukun; Lei, Yanqi; Dai, Zhuojun; Luo, Changfang; Gong, Qiming; Li, Yanqun; Xu, Yong; Huang, Wei (Frontiers in Immunology, 2025)
Recent studies have revealed that the innate immune system possesses the capacity to develop “trained immunity” via metabolic and epigenetic reprogramming, leading to non-specific memory responses distinct from the memory traditionally attributed exclusively to adaptive immunity. Hyperglycemia, acting as an initiating stimulus, drives myeloid progenitor cell proliferation and monocyte-derived macrophage expansion, which leads to a sustained pro-inflammatory phenotype that is closely associated with the pathogenesis of diabetes and its related complications. The paradigm of trained immunity provides a novel perspective on explaining the “metabolic memory” phenomenon in diabetes. Here, we summarize the research progress on trained immunity, diabetes, and related complications to explore novel insights into diabetes prevention and treatment.